ANALISIS PERTIMBANGAN HAKIM TERHADAP PUTUSAN SELA DALAM PERKARA ISBAT NIKAH NO. 1009/Pdt.P/2018/PA.Kab.Mlg. - Ali Akbar Ruhullah Muhammadi; Ibnu Jazari; Khoirul Asfiyak (Jurnal Hikmatina, 2020)
Tussen Vonnis (Interlocutory Verdict) is a term used for decisions rendered still in trial before the final verdict. This term can be traced since the Dutch legal period listed in Rechtsreglement voor de Buitengewesten (R.Bg.) and Het Herziene Inlandsch Reglement (HIR). Over time and the increasingly rapid development of law in Indonesia so that the term stipulation for cases (voluntair) in addition to the term that has been used is the decision for the case (contentious). In the study of this interim decision, the researcher used a familiar methodology, namely a qualitative research method. The analysis technique used is descriptive juridical analysis which will clearly analyze legally how the term interlocutory verdict is actually not appropriate to use in this case (voluntair) so it is necessary to bring up the term interlocutory determination, thus it is in accordance with judicial logical thinking. Tussen Vonnis (Interim Decision) is term Keywords: interlocutory verdict, judges consideration, juridical analysis